OPTIMIZATION OF ULTRASOUND ASSISTED EXTRACTION OF POLYPHENOLS IN COCOA BEANS - Fajardo Daza, Jonny Ariel; Herrera Ruales, Frank Carlos; Ibarra Cabrera, Carol Andrea; Arturo Perdomo, David (Vitae, 2020)
Background: The determination of polyphenols in cocoa beans allows the establishing of antioxidant properties of great benefit to this product. Objectives: Optimization of the ultrasound-assisted extraction method to determine the content of polyphenols in cocoa beans. Methods: Two experiments design stages were carried out to optimize the ultrasound-assisted extraction process of polyphenols from the cocoa bean. In the first experiment design stage, the adequate extraction solvent was determined; for this purpose, five types of solvents were evaluated through a completely random design unrestricted (CRD). In the second experiment stage, a central composite design 22 + star point (with two central points) was used, which was evaluated using the response surface methodology to determine the influence of the temperature, time, and solute / solvent ratio. Results: The experiment found that acetone: water: acetic acid (70: 29.5: 0.5) mixture, leads to a greater amount of total extracted phenols measured for the Folin-Ciocalteu method. Analysis of variance (ANOVA) found that six significant effects that influence the response variable (total phenols extracted). The main effects were of the three factors and three of their interactions. Conclusions: After the optimizing said factors, an optimal point was found: 39.3 °C oftemperature, 74.5 minutes, and 22.8 mL of solvent per gram of cocoa sample.